Social values and the corruption argument against financial incentives for healthy behaviour - Brown, Rebecca C H (J Med Ethics, 2017)
Financial incentives may provide a way of reducing the burden of chronic diseases by motivating people to adopt healthy behaviours. While it is still uncertain how effective such incentives could be for promoting health, some argue that, even if effective, there are ethical objections that preclude their use. One such argument is made by Michael Sandel, who suggests that monetary transactions can have a corrupting effect on the norms and values that ordinarily regulate exchange and behaviour in previously non-monetised contexts. In this paper, I outline Sandel's corruption argument and consider its validity in the context of health incentives. I distinguish between two forms of corruption that are implied by Sandel's argument: efficiency corruption and value corruption. While Sandel's thought-provoking discussion provides a valuable contribution to debates about health policies generally and health incentives specifically, I suggest the force of his criticism of health incentives is limited: further empirical evidence and theoretical reasoning are required to support the suggestion that health incentives are an inappropriate tool for promoting health. While I do not find Sandel's corruption argument compelling, this only constitutes a partial defence of health incentives, since other criticisms relating to their use may prove more successful.